Peran Extended Focused Assessment with Sonography for Trauma (eFAST) pada Pasien Trauma Toraks dan Abdomen: Teknik - Nathania, Liem Marcella (PT Kalbe Farma Tbk., 2025)
Trauma is the biggest cause of death in young people. Among these traumas, 80% are blunt traumas, mostly to the thorax and abdomen. Blunt trauma can cause bleeding, which increases mortality. Prompt intervention can reduce mortality. eFAST (extended focused assessment with sonography for trauma) is a bedside ultrasound examination indicated for abdominal and thoracic trauma patients, which is limited to 4 examination windows in the abdomen to evaluate for hemoperitoneum, hemothorax, and pericardial effusion. The eFAST examination uses ultrasound equipment that is widely available in the emergency department and can be performed bedside, making it less time-consuming. eFAST has a high sensitivity and specificity, which is helpful in its role as a screening modality. The eFAST examination has many advantages, such as ease of use, being noninvasive, being fast, being easy to find, and not using radiation or contrast material, making it safe for children and pregnant women, and being inexpensive. The eFAST examination is important for the diagnosis of thoracoabdominal trauma, as it enables rapid screening.